Electronic Nematic States Tuned by Isoelectronic Substitution in Bulk FeSe1−xSx - Coldea, Amalia I. (Frontiers in Physics, 2021)
Isoelectronic substitution is an ideal tuning parameter to alter electronic states and correlations in iron-based superconductors. As this substitution takes place outside the conducting Fe planes, the electronic behaviour is less affected by the impurity scattering experimentally and relevant key electronic parameters can be accessed. In this short review, I present the experimental progress made in understanding the electronic behaviour of the nematic electronic superconductors, FeSe 1−x S x . A direct signature of the nematic electronic state is in-plane anisotropic distortion of the Fermi surface triggered by orbital ordering effects and electronic interactions that result in multi-band shifts detected by ARPES. Upon sulphur substitution, the electronic correlations and the Fermi velocities decrease in the tetragonal phase. Quantum oscillations are observed for the whole series in ultra-high magnetic fields and show a complex spectra due to the presence of many small orbits. Effective masses associated to the largest orbit display non-divergent behaviour at the nematic end point (x ∼ 0.175(5)), as opposed to critical spin-fluctuations in other iron pnictides. Magnetotransport behaviour has a strong deviation from the Fermi liquid behaviour and linear T resistivity is detected at low temperatures inside the nematic phase, where scattering from low energy spin-fluctuations are likely to be present. The superconductivity is not enhanced in FeSe1−xSx and there are no divergent electronic correlations at the nematic end point. These manifestations indicate a strong coupling with the lattice in FeSe1−xSx and a pairing mechanism likely promoted by spin fluctuations.